Virtual ultrasound machine operating in a GHz to MHz frequency range for particle-based biomedical simulations - Urban Čoko; Tilen Potisk; Matej Praprotnik (Proceedings of the National Academy of Sciences, 2026)
Ultrasound–matter interactions underpin numerous biomedical and soft-matter applications, yet simulating these phenomena is challenging due to the large separation of viscous and sonic time scales. Continuum methods capture large-scale wave propagation but cannot resolve microscale interactions, while particle-based approaches offer molecular resolution but struggle with efficiency and stability at larger scales. We introduce a particle-based virtual ultrasound machine that uses a smoothed dissipative particle dynamics variant with an implicit pressure solver and a negative-pressure stabilization scheme, required to mimic acoustic propagation across medically relevant MHz–GHz frequencies. We demonstrate its capabilities by modeling the acoustophoresis of encapsulated microbubbles, a key mechanism in ultrasound-mediated drug delivery. Beyond this application, the approach establishes a generalizable platform for simulating wave–matter interactions in soft and biological materials, opening promising directions for computational studies of acoustics-driven phenomena in science and engineering.